Behçet’s Disease : A Clinical Review (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Behcet’s disease (BD) is a rare relapsing systemic inflammatory disorder with a chronic, relapsing-remitting course of unknown etiology, current knowledge suggests that BD could follow an autoimmune process triggered by an infectious or environmental agent in genetically predisposed individuals. BD has been hallmarked predominantly by oral aphthosis, genital ulcers, and chronic relapsing bilateral uveitis, all of which represent the “stigmata” of disease. However, many other organs including the vascular, neurological, musculoskeletal, and gastrointestinal systems can be affected. BD occurs most frequently in Eurasian populations along the ancient trading route known as the “Silk Road” which extends from eastern Asia to the Mediterranean basin. The diagnosis of BD is only supported by clinical criteria and requires the exclusion of other diagnoses based on clinical presentation. There are no pathognomonic laboratorial findings of BD. This rare disease often leads to blindness and fatal systemic involvement. Main causes of death include major vessel disease and central nervous system involvement. Corticosteroids are commonly used to treat clinical manifestations of BD in combination with immunosuppressant drugs. Tumor necrosis factor (TNF)-blocking agents such as Infliximab, Etanercept, and Adalimumab have been reported to have success in patients with BD.